Direct hard X-ray photodetector with superior sensitivity based on ZnGa2O4 epilayer grown by metalorganic chemical vapor deposition - Siddharth Rana; Shang-Jui Chiu; Chih-Yang Huang; Fu-Gow Tairtan; Yan-Gu Lin; Dong-Sing Wuu; Jitendra Pratap Singh; Guang-Cheng Su; Po-Liang Liu; Ray-Hua Horng (Materials Today Advances, 2023)
In this work, we have fabricated a highly sensitive direct irradiating X-ray photodetector (DXPD) based on Zinc Gallium Oxide (ZnGa2O4) epilayers with a metal-semiconductor-metal structure. The ZnGa2O4 epilayers were grown on a c-plane sapphire substrate by metalorganic chemical vapor deposition (MOCVD). To test the DXPD's capabilities, we subjected it to a synchrotron hard X-ray source with an energy of 10 keV, and measured incident radiation flux ranging from 5.7✕107 to 4.6 ✕1011 counts/sec. The effect of changing the applied bias voltage on the time response of the DXPD was investigated. The sensitivity of hard XPDs was compared using gallium oxide (β-Ga2O3) epilayer grown by MOCVD. The results showed that ZnGa2O4 DXPD had approximately 104 times greater sensitivity than the β-Ga2O3 based XPD. ZnGa2O4 based detectors also exhibited remarkable sensitivity of 2.87 × 109 μC Gyair−1cm−2 for the incident flux of 5.7✕107 counts/sec at 15 V. Additionally, the sensitivity was examined in terms of applied bias and dose rate. Based on these observations, it can be concluded that ZnGa2O4 epilayers grown by MOCVD hold immense potential for use in high-performance hard XPDs.